PERBANDINGAN SISTEM PEMERINTAHAN PRANCIS-INDONESIA PADA MASA PEMERINTAHAN JOKOWI DAN EMMANUEL MACRON - Nazara, Adinda Mustika (Universitas Panca Marga, 2023)
Each country in regulating the course of its government uses a different system of government, the state and the system of government are a unit where state institutions work and relate to each other, where each state institution must carry out its duties as well as possible so that the goals of a country are managed to organize and realize the welfare of society and the interests of the state. Likewise with the countries of Indonesia and France with their respective heads of state. The Indonesian government system led by President Jokowidodo can be seen from the government model that President Joko Widodo wants to carry out, similar to the style of government during Soekarno's time where Soekarno's great desire was to want Indonesia to become an Asian tiger to become a big country that is feared by other countries in the world. Proximity to the people by going directly to the people in the regions to see firsthand the condition of the people and see firsthand the work of the ministers. Meanwhile, the French government system led by Emmanuel Carnos has a leadership style that is closer to borrowing the leadership style concept of Jerrold Post, Hermann and Hudson as conciliators. Keywords: Government System, Conciliator, Asian Tiger